Drop jump vertical kinetics identify male youth soccer players at greater risk of non-contact knee injury - Pedley, J. S.; Lloyd, R. S.; Read, P. J.; Moore, I. S.; Myer, G. D.; Oliver, J. L. (Physical Therapy in Sport, 2025)
Objectives: To determine associations between drop-jump vertical kinetics and acute non-contact knee injury-risk in male youth soccer players. Design: Prospective cohort study. Setting: Professional soccer academies. Participants: Youth soccer players (n = 264). Main outcome measures: Drop-jump vertical kinetics; injury epidemiology. Associations between kinetics and injury were assessed using binary logistic regression. Differences between injured and uninjured groups were compared using statistical parametric mapping. Results: Peak braking: peak propulsive force ratio (OR = 1.59, 1.10-2.29, p < 0.05), propulsive work (OR = 0.53, 0.28-0.99, p < 0.05) and vertical stiffness (OR = 1.68, 1.13-2.52, p < 0.05) were associated with risk of sustaining a knee injury. All variables demonstrated `unusable` or `weak` levels of predictive ability in identifying players who would become injured (AUC 0.568-0.663). Conclusions: Drop-jump vertical kinetics that characterise the shape of the force-time waveform provide insight to acute non-contact knee injury-risk in male youth soccer players. Large transient spikes in force in the early phase of ground contact, coupled with reduced propulsive forces are a risk factor for acute non-contact knee injury in male youth soccer players. Variables are not sensitive enough to predict injury but provide additional training targets to help mitigate risk in this population.